2017
DOI: 10.7717/peerj.3500
|View full text |Cite
|
Sign up to set email alerts
|

Diverse habitat use during two life stages of the critically endangered Bahama Oriole (Icterus northropi): community structure, foraging, and social interactions

Abstract: Our ability to prevent extinction in declining populations often depends on effective management of habitats that are disturbed through wildfire, logging, agriculture, or development. In these disturbed landscapes, the juxtaposition of multiple habitat types can be especially important to fledglings and young birds, which may leave breeding grounds in human-altered habitat for different habitats nearby that provide increased foraging opportunities, reduced competition, and higher protection from predators. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…These species may have suffered declines due to some of the same threats that face the Bahama Oriole, including cowbird parasitism (Lovette et al 1999). Although Shiny Cowbirds have been observed on Andros (Baltz 1996) and have been recorded parasitizing Bahama Oriole nests in anthropogenic habitats (Price et al 2011;KEO, unpublished data), cowbird observations in other habitats remain sparse (Price and Hayes 2017;KEO, unpublished data).…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These species may have suffered declines due to some of the same threats that face the Bahama Oriole, including cowbird parasitism (Lovette et al 1999). Although Shiny Cowbirds have been observed on Andros (Baltz 1996) and have been recorded parasitizing Bahama Oriole nests in anthropogenic habitats (Price et al 2011;KEO, unpublished data), cowbird observations in other habitats remain sparse (Price and Hayes 2017;KEO, unpublished data).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…One survey conducted in February 2002 found orioles in moderate densities in mixed pine/coppice and low densities in pure coppice but did not report any orioles in pure pine forest (Currie et al 2005). A survey conducted in July 2005 found that the orioles use both coppice and pine habitats but suggested that they occur in higher density in coppice (Price and Hayes 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Our study focused on the pine forests in North Andros (Fig. 1), which were logged heavily in the mid-1900s (Henry 1974, Price andHayes 2017). The pine forest vegetation includes Caribbean pines and an understory of Key thatch palms, poisonwood (Metopium toxiferum), ferns, and other broadleaf shrubs (Stonko et al 2018).…”
Section: Study Areamentioning
confidence: 99%
“…In developed areas on Andros, many coconut palms (Cocos nucifera), an important nest tree for Bahama Orioles along the settled east coast, have been killed by lethal yellowing disease (Price et al 2015). Logging and residential development have caused the orioles to lose native pine forest habitat as well (Price and Hayes 2017).…”
mentioning
confidence: 99%